STUDIES ON THE STABILITY OF GRAIN WEIGHT PER PLANT IN AUTUMN OAT (AVENA SATIVA L.) - MADOSA, Emilian; CIULCA, Sorin; VELICEVICI, Giancarla; CIULCA, Adriana; SASU, Lavinia; POPESCU, Sorina; AVADANEI, Constantin (Journal on Processing and Energy in Agriculture, 2022)
The aim of the study was to assess the stability of the weight grains per plant in the autumn oats. The study was conducted over three years, examining of 73 autumn oat genotypes. The experimental data was processing performed several linear regression models. The values determined varied according to the genotype and climatic conditions of the experimental year. The grain production/plant had the highest stability and the lowest interaction genotype x environment to Valiant, Solva, 4484, Emperor genotypes. The high values of grain weight per plant are associated with good stability in the Blamouth, PA725-6113 genotypes. A strong influence of the interaction genotype x environment was found in the genotypes Boer, Marettos Anderson, PA621-3274. In the use of autumn oat germplasm to improve the grains production on the plant, the genotype has a decisive role. The imperfect correlations influence the interaction genotype x environment in a proportion of 66.5%.